Odpowiedź:
[tex]$G(s)=\frac{2\cdot s+\frac{1}{2} }{s^2+7\cdot s+10}$[/tex]
Szczegółowe wyjaśnienie:
[tex]$2\cdot \frac{\mathrm{d}^3}{\mathrm{d}t^3} y(t)+14\cdot \frac{\mathrm{d}^2}{\mathrm{d}t^2} y(t)+20\cdot \frac{\mathrm{d}}{\mathrm{d}t} y(t)=4\cdot \frac{\mathrm{d}^2}{\mathrm{d}t^2} u(t)+ \frac{\mathrm{d}}{\mathrm{d}t} u(t)$[/tex]
Poddajemy obustronnej transformacie Laplace'a, pamiętając, że:
[tex]$F(s)=\mathcal{L}\{f(t)\}=\int\limits^{\infty}_0 {\mathrm{e}^{-st}}f(t) \, \mathrm{d}t $[/tex]
Gdzie [tex]s[/tex] jest operatorem Laplace'a (zmienną zespoloną).
Otrzymujemy więc:
[tex]$\bigg(2\cdot s^3+14\cdot s^2+20\cdot s\bigg)\cdot Y(s)=\bigg(4\cdot s^2+s\bigg)\cdot U(s) $[/tex]
Wyznaczamy transmitancję:
[tex]$G(s)=\frac{Y(s)}{U(s)}=\frac{4\cdot s^2+s}{2\cdot s^3+14\cdot s^2+20\cdot s}=\frac{2\cdot s+\frac{1}{2} }{s^2+7\cdot s+10}$[/tex]